Exploring the Gating Mechanism of the Human Copper Transporter, hCtr1, Using EPR Spectroscopy - Shahaf Peleg; Shelly Meron; Yulia Shenberger; Lukas Hofmann; Lada Gevorkyan-Airapetov; Sharon Ruthstein (Biomolecules)
Ctr1 is a membrane-spanning homotrimer that facilitates copper uptake in eukaryotic cells with high affinity. While structural details of the transmembrane domain of human Ctr1 have been elucidated using X-ray crystallography and cryo-EM, the transfer mechanisms of copper and the conformational changes that control the gating mechanism remain poorly understood. The role of the extracellular N-terminal domains is particularly unclear due to the absence of a high-resolution structure of the full-length hCtr1 protein and limited biochemical and biophysical characterization of the transporter in solution and in cell. In this study, we employed distance electron paramagnetic resonance to investigate the conformational changes of the extracellular N-terminal domain of full-length hCtr1, both in vitro and in cells, as a function of Cu(I) binding. Our results demonstrate that at specific Cu(I) concentrations, the extracellular chains move closer to the lumen to facilitate copper transfer. Additionally, while at these concentrations the intracellular part is penetrating the lumen, suggesting a ball-and-chain gating mechanism. Moreover, this phenomenon was observed for both reconstituted protein in micelles and in native cell membranes. However, the measured distance values were slightly different, suggesting that the membrane’s characteristics and therefore its lipid composition also impact and even regulate the gating mechanism of hCtr1.